2014
DOI: 10.1038/mp.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Brain-specific Foxp1 deletion impairs neuronal development and causes autistic-like behaviour

Abstract: Neurodevelopmental disorders are multi-faceted and can lead to intellectual disability, autism spectrum disorder and language impairment. Mutations in the Forkhead box FOXP1 gene have been linked to all these disorders, suggesting that it may play a central role in various cognitive and social processes. To understand the role of Foxp1 in the context of neurodevelopment leading to alterations in cognition and behaviour, we generated mice with a brain-specific Foxp1 deletion (Nestin-CreFoxp1−/−mice). The mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 38 publications
4
109
0
Order By: Relevance
“…Normally, mouse pups subvocalize when separated from their mother; Foxp2 −/− pups do not exhibit this behavior, and Foxp2 +/− pups show a reduction (Shu et al, 2005). No alterations in vocalization were reported for mice with a brain-specific deletion of Foxp1; however, these mice exhibit abnormal cognitive and social behavior, echoing phenotypes in patients with FOXP1 mutations (Bacon et al, 2015).…”
Section: The Foxp Family: Language Acquisition and Cognitive Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…Normally, mouse pups subvocalize when separated from their mother; Foxp2 −/− pups do not exhibit this behavior, and Foxp2 +/− pups show a reduction (Shu et al, 2005). No alterations in vocalization were reported for mice with a brain-specific deletion of Foxp1; however, these mice exhibit abnormal cognitive and social behavior, echoing phenotypes in patients with FOXP1 mutations (Bacon et al, 2015).…”
Section: The Foxp Family: Language Acquisition and Cognitive Functionmentioning
confidence: 96%
“…Tissuespecific deletions of FoxP factors also result in developmental defects. For example, mice with a deletion of Foxp1 in neurons are viable but display a morphological change in the striatum and hippocampus (Bacon et al, 2015).…”
Section: The Foxp Family: Language Acquisition and Cognitive Functionmentioning
confidence: 99%
“…Therefore, understanding how FOXP1 functions within the brain should allow for key insights into the molecular pathways at risk in ASD. Several reports have begun to elucidate a role for Foxp1 in the brain (Rousso et al 2012;Tang et al 2012), and recent work has shown that mice with brain-specific loss of Foxp1 have altered hippocampal electrophysiology, striatal morphology, and social behaviors (Bacon et al 2015). However, the region-specific transcriptional profile of Foxp1 in the mouse brain, how well this profile is conserved in human-relevant Foxp1 haploinsufficient models, and the behavioral consequences of disrupting these regional gene networks remain largely unknown.…”
mentioning
confidence: 99%
“…Therefore, these interactions have not been shown in model 4 (Figure 5d) again. FOXP1 (forkhead box protein P1) deletions [98,99] and increase [100] have both been associated with ASD. Both FOXP1 [101] and FOXP2 can downregulate CNTNAP2 (Contactin-associated protein-like 2) [100,102], another candidate gene of ASD [67].…”
Section: Foxp2 and Mir-3666 May Be Responsible For The Pathogenesis Omentioning
confidence: 99%